Electronic Properties of Au/MgF2/Au Structures at Different Temperatures: Electronic Properties of Au/MgF2/Au (Biological Sciences - PJSIR, 2010)
Investigations of some electronic properties of vacuum evaporated thin film Au/MgF /Au structures such  as circuiting Ic  and emission Ie  currents versus the applied voltage, electron attenuation lengths MgF2   layers and the role   of the latter layers showed that these devices undergo an electroforming process leading to decrease in resistivity of several orders of magnitude along with a negative resistance region in their I-V characteristics. High emission current densities are archived for low applied voltages with the cathodes at or near the room temperature. By decreasing the temperature, both Ic and Ie decreased and at low temperatures the negative resistance region disappears completely. High values of hot electron attenuation lengths in the insulator were obtained and the significance of these high valuesis described.